2020
DOI: 10.1155/2020/7058145
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Blood Glucose Level Predicts Postsurgical Gastroparesis Syndrome after Subtotal Gastrectomy: Development of an Individualized Usable Nomogram

Abstract: Background. Postsurgical gastroparesis syndrome (PGS) after subtotal gastrectomy imposes significant social and economic burdens. We aimed to investigate the relationship between preoperative blood glucose level and PGS and develop a nomogram for individualized prediction. Patients and Methods. We retrospectively analyzed 633 patients with gastric cancer who underwent subtotal gastrectomy. Preoperative blood glucose levels were evaluated via receiver operating characteristic (ROC) curve analysis. Chi-squared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…Unlike previous studies that demonstrated that poor perioperative glycemic control was related to worse postoperative outcomes in nondiabetic patients after gastric surgery [2,6,17], no signi cant difference was found between perioperative HG, whether preoperative or postoperative, and postoperative complications in the total population. Considering the different in uences of the normal physiological anatomy of the digestive tract on postoperative blood glucose levels in various anastomotic methods after radical gastrectomy, we subdivided the cohort into Billroth-I and non-Billroth-I groups.…”
Section: Discussioncontrasting
confidence: 96%
“…Unlike previous studies that demonstrated that poor perioperative glycemic control was related to worse postoperative outcomes in nondiabetic patients after gastric surgery [2,6,17], no signi cant difference was found between perioperative HG, whether preoperative or postoperative, and postoperative complications in the total population. Considering the different in uences of the normal physiological anatomy of the digestive tract on postoperative blood glucose levels in various anastomotic methods after radical gastrectomy, we subdivided the cohort into Billroth-I and non-Billroth-I groups.…”
Section: Discussioncontrasting
confidence: 96%
“…We believe that RY reconstruction with a small remnant stomach helps reduce the incidence of DGE. However, in contrast, the incidence of functional DGE (also known as RSS) following RY reconstruction is reportedly higher than that after Billroth I reconstruction 18 , 19 . Many causes of RSS have been proposed, including ectopic pacemakers originating in the Roux limb, driving contractions in a reverse direction, and gastroparesis of the remnant stomach after vagotomy 20 22 .…”
Section: Discussionmentioning
confidence: 90%
“…Since it is difficult to achieve strict glycemic control in the postsurgical period due to unstable food intake and continuous intravenous infusion, some patients develop a hyperglycemic condition, which in turn may lead to DGE. Mao et al reported that preoperative hyperglycemia, rather than hemoglobin A1c levels, could effectively predict DGE following subtotal gastrectomy and presented a model that incorporated multiple risk factors to predict postsurgical gastroparesis 18 . Considering the physiological relationship between hyperglycemia and DGE, such a predictive model can prove especially useful.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative hyperglycemia is associated with an increased risk of postoperative complications (Davis et al 2012 ; Mao et al 2020 ; Noordzij et al 2007 ). Hyperglycemia can often occur before surgery in diabetic patients(glycemic poor control) and non-diabetic patients(unrecognized DM or stress).…”
Section: Discussionmentioning
confidence: 99%